Influence Well-being Employees and the Environment Work Employee on the Performance of PT XYZ Employees in Bandung - Cantika Putri Apriliani; Abdullah, Muhamad Al Faruq (Greenation International Journal of Law and Social Sciences, 2024)
Study This is studies quantitative use? method descriptive and verification. In research this, testing hypothesis done through testing continued simultaneously? with testing Partial. In section verification research, found that Pearson correlation between variable Well-being Employees (X1) and Environment Work Employee (X2) has coefficient correlation (rx1x2) of 0.717, or 71.7% if stated in percentage. Use device SPSS version 23 software, known that coefficient track for variable Well-being Employee (X1) to Employee Performance (Y) is 0.550 or 55.0%. It means Well-being Employees and the Environment Work Employee in a way together affecting employee performance at PT. XYZ in Bandung was 70.6% (R square value), while the other 29.4% influenced by other factors that are not researched. Coefficient track For Well-being Employee on Employee Performance is 0.550, while coefficient track Environment Work Employee on Employee Performance is 0.354. Variables that don't researched own influence amounting to 29.4%. With equality the, total influence or combined from influence direct or not direct Environment Work Employees (X2) to Employee Performance (Y) are of 0.264 or 26.4%. It means that in a way partial, Environ Work Employee influential on Employee Performance. Positive value show that connection between second variable is unidirectional; If Environment Work Employee increases, then employee performance also increases, and vice versa.